Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21608/fjard.2019.190568
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ammonium Nitrate and Potassium Humate on Chemical Composition of Calendula Officinalis, L. Plant Under Two Types of Soil Conditions

Abstract: An experiment was conducted during 2015/2016 and 2016/2017 growing seasons at the Experimental Farm of Faculty of Agriculture, Fayoum University, Fayoum. The experiment aimed to study the influence of ammonium nitrate and potassium humate on chemical composition of Calendula officinalis, L. plant under two types of soil. The laid-out in a splitsplit plot arranged in randomized complete block design with three replicates. Soil media was considered as main plot in form of two types (clay & sand loamy soils), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Generally, the greatest values were achieved with the interaction treatment of salinized water at 1.4 dS/m in combination with potassium humate at 3000 ppm. Similar findings were recorded by Burhan and Al-Taey (2018) on dill and Badran et al (2019) on calendula plant. For essential oil percentage, the relationship between the main and subplot treatments was substantial in both cuts during both seasons.…”
Section: Vegetative Growth Parameterssupporting
confidence: 87%
See 1 more Smart Citation
“…Generally, the greatest values were achieved with the interaction treatment of salinized water at 1.4 dS/m in combination with potassium humate at 3000 ppm. Similar findings were recorded by Burhan and Al-Taey (2018) on dill and Badran et al (2019) on calendula plant. For essential oil percentage, the relationship between the main and subplot treatments was substantial in both cuts during both seasons.…”
Section: Vegetative Growth Parameterssupporting
confidence: 87%
“…It has been suggested that potassium humate is a workable and affordable solution for restoring damaged land resources. Additionally, studies by Said-Al Ahl et al (2009), Badran et al (2019), Shyala et al (2019), Wei et al (2021), and Shalaby et al (2023) have shown that potassium humate is a common organic fertilizer that may be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors proved the positive effects of potassium humate e.g. Heikal (2017) on Salvia farinacea, Shyala et al (2019) on Tagetes erecta, Noor El-Deen and El-Ashwah (2019) on Asparagus densiflorus 'Meyerii', Badran et al (2019) on Calendula officinalis and Mohamed and Ghatas (2021) on Achillea millefolium.…”
Section: Introductionmentioning
confidence: 99%